(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
Communication is vital for human existence. In all social structures and cultural practices, communication is very important. The development of culture and society is greatly influenced by how individuals interact, interpret information, and communicate with one another. The last few years have seen significant development in the field of Information and Communication Systems. These systems have changed the way people communicated a few years back. It is not only the communication pattern but these systems have immense capacity to create, capture, compute and distort information just in a matter of seconds. This has posed a big challenge to existing society and culture. As with every change in the way we consume and communicate information, there is a new struggle over meaning, significance, knowledge, and power. Old rules, orders, and beliefs cannot be applied perfectly under the new regime and thus formations of power, significance, and meaning of knowledge are all under threat from these changes. This work is an attempt to study these new means of information and communication systems in terms of their impact on our society and culture. The study is concentrated on understanding how ICT, New media, and Internet are playing their roles in our cultural formation and adaptation of society. The concluding part of this work is to see the role of these technologies in the current scenario and draw conclusions from them.